Parent and provider perspectives on recently incarcerated youths' access to healthcare during community reentry. (March 2020) - Barnert, Elizabeth S.; Abrams, Laura S.; Lopez, Nathalie; Sun, Ava; Tran, John; Zima, Bonnie; Chung, Paul J.
Highlights: Parents and providers agreed on solutions for increasing care access during reentry. Systems priorities include care continuity and overcoming transportation barriers. Eliminating Medicaid coverage gaps during reentry was viewed as a policy priority. Overall, parents play an essential role in linking youth to care during reentry. Longer-term strategies to enhance family engagement in care are also needed. Abstract: Incarcerated youth have numerous healthcare needs, yet access to healthcare following community reentry is limited. Healthcare and juvenile justice providers, along with parents, strongly influence access to care for youth undergoing reentry. However, their perspectives are often missing from the literature. We examined parent and provider perspectives on youths' access to healthcare during community reentry. We conducted 72 longitudinal interviews with parents of youth undergoing reentry (n = 34 parents) and cross-sectional interviews with health and juvenile justice providers (n = 20 providers). We performed inductive analysis of interview transcripts to identify the major themes related to access to healthcare during reentry. Respondents identified key leverage points that influence access to healthcare along the spectrum of individual, community, and policy-level factors. Parent and provider perspectives demonstrated substantial overlap, strongly concurring on the essential role of parents in linking youth to care and the external factors that limit parents' ability to connect youth to care. However, providers discussed parents not buying-in to treatment plans as a barrier to care, and parents uniquely described feeling powerless when their children were not motivated to receive care. Parents and providers agreed on priority solutions for improving care access during reentry. Immediate solutions centered on: (1) increasing reliability and continuity of providers, (2) providing free or low-cost transportation to healthcare visits, and (3) eliminating gaps in Medicaid coverage post-incarceration. Findings also signal the broader need to pursue strategies that increase family engagement in healthcare during reentry. In doing so, health and juvenile justice providers can partner with parents to overcome barriers to healthcare for youth during reentry.